Evaluasi Kepuasan Pengguna Layanan Aplikasi Jago Syariah dengan Metode Servqual - Nandika, Moh Dimas; Irnawati, Oky (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2025)
PT. Bank Jago Tbk, formerly known as PT. Bank Artos Indonesia Tbk, was established in 1992. In response to the operational restrictions during the Covid-19 pandemic in 2020, the bank underwent a digital transformation. One of its major innovations was mobile banking, which enables customers to perform financial transactions using smartphones or other mobile devices. This service has attracted significant interest across the banking industry. A key factor in the sustainability of such applications is user satisfaction. This study aims to assess the level of customer satisfaction with the Bank Jago mobile application to support improvements in service quality and overall user experience. The research employed the Servqual approach, measuring five dimensions—Tangible, Reliability, Responsiveness, Assurance, and Empathy—using a Likert scale and analyzed with SPSS. A total of 96 respondents participated in the study. The results, based on the Servqual model, show that the Tangible dimension scored 79.86%, Reliability 79.17%, Responsiveness 79.79%, Assurance 78.02%, and Empathy 80%, with all scores indicating strong agreement. The lowest score was found in the Assurance dimension, suggesting that aspects of trust and user security could be improved. The study concludes that users in Bogor are generally satisfied with the Bank Jago mobile application, although there remains room for enhancement, particularly in building user confidence and a sense of security. The contribution of this research lies in providing a quantitative overview of user perceptions regarding service quality in a digital Islamic banking application, which may serve as a foundation for developing improved features and communication strategies.